Interpretasi Kontemporer tentang Riba dan Relevansinya dengan Bunga Bank - Mugiyati Mugiyati (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2009)
The debate whether interest is riba or not remains a hot issue up until today. Various interpretation of riba in relation to interest results from the ratio legis (â€˜illat) proposed by the medieval jurists seems to be no longer inaccurate within the discourse of contemporary Islamic law.Meanwhile, several trends concerning current economic activities such as the role of bank as financial intermediation had not been discussed in medieval jurisprudence although simple form of riba with all of its nature and impact had been understood.According to contemporary Islamic jurists, the relevance of riba to interest is viewed from various perspectives which lead to different legal status. There are at least two paradigm as a reference in viewing this issue: (1) legal formalÂ  which inductively understands interest employing qiyas. (2) contextual paradigm which deductively sees interest within a given context and situation.Â